2012
DOI: 10.4028/www.scientific.net/amr.576.467
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of TIG Melted Composite Coating on Steel Produced Using 1.0 and 1.5 mg/mm<sup>2</sup> TiC at an Energy Input of 2640 J/mm

Abstract: Surface modification by reinforcing ceramic particulates can give protection against wear and corrosion of metal. In this work, two different amounts of TiC powder of nominal size 45 to 100 µm were embedded on AISI 4340 steel surfaces by melting under a Tungsten Inert Gas (TIG) welding torch with an energy input of 2640 J/mm. The microstructure, geometry and hardness of the single track composite layers were investigated. The resolidified melt tracks were hemispherical in shape. With increasing TiC content, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…These types of TiC distribution and segregation have also been reported in laser processed MMC coatings on titanium surfaces 7 and TIG torch processed coatings on titanium and steel surfaces. 21,27,[32][33][34][35] TiC precipitates of globular, cubic and flower morphologies were seen in many overlapping tracks, but were not uniformly distributed in the melt microstructures. Similar morphologies of TiC precipitates were also reported in single track composite coatings.…”
Section: Microstructurementioning
confidence: 99%
“…These types of TiC distribution and segregation have also been reported in laser processed MMC coatings on titanium surfaces 7 and TIG torch processed coatings on titanium and steel surfaces. 21,27,[32][33][34][35] TiC precipitates of globular, cubic and flower morphologies were seen in many overlapping tracks, but were not uniformly distributed in the melt microstructures. Similar morphologies of TiC precipitates were also reported in single track composite coatings.…”
Section: Microstructurementioning
confidence: 99%
“…Altering working distances in favour to have less or more melt involved no additional cost. Our experimental work showed that fusing the TIG arc at certain heat input of 1 mm working distance is limited to give dissolution of the TiC on the AISI 4340 low alloy steel substrate [9]. This work delivers information of melt pool sizes with regards to their HAZ, defects, microstructural features, and microhardness from used working distances at 0.5 mm and 1.5 mm.…”
Section: Introductionmentioning
confidence: 76%
“…Minitab 17 software was used to determine the no. of experiments to be conducted with the predetermined variables and their levels [5]. The optimum setting is the parameter combination, which has the highest S/N ratio [7].…”
Section: Methodsmentioning
confidence: 99%
“…This is because of high heat input resulted higher temperature of melt during TIG welding. This higher temperature melt has lower solidification rate which assists the melt to move towards the substrate thus producing larger melt pool [5].…”
Section: Melt Pool Dimensionmentioning
confidence: 99%
See 1 more Smart Citation